A practical guide to measuring functional indicators and traits in biocrusts. (19th July 2019) - Mallen‐Cooper, Max; Bowker, Matthew A.; Antoninka, Anita J.; Eldridge, David J.
Abstract : Biocrusts are multifunctional communities that are increasingly being used to restore degraded or damaged ecosystems. Concurrently, restoration science is shifting away from the use of purely structural metrics, such as relative abundance, to more functional approaches. Although biocrust restoration technology is advancing, there is a lack of readily available information on how to monitor biocrust functioning and set appropriate restoration goals. We therefore compiled a selection of 22 functional indicators that can be used to monitor biocrust functions, such as CO2 exchange as an indicator of productivity or soil aggregate stability as a proxy for erosion resistance. We describe the functional importance of each indicator and the available protocols with which it may be measured. The majority of indicators can be measured as a functional trait of species by using patches of biocrust or cultures that contain only one species. Practitioners wishing to track the multifunctionality of an entire biocrust community would be advised to choose one indicator from each broad functional group (erosion resistance, nutrient accumulation, productivity, energy balance, hydrology), whereas a targeted approach would be more appropriate for projects with a key function of interest. Because predisturbance data are rarely available for biocrust functions, restoration goals can be based on a closely analogous site, literature values, or an expert elicitation process. Finally, we advocate for the establishment of a global trait database for biocrusts, which would reduce the damage resulting from repeated sampling, and provide a wealth of future research opportunities.